Preparation, Structural and Dielectric Properties of (1-x) Pb(Zr0.52Ti0.48)O3–x BiFeO3 Composites - AHABBOUD Malika; gouitaa Najwa; Ahjyaje Fatimazahra; lamcharfi taj-dine; Abdi Farid; Haddad Mustapha (Iranian journal materials science and engineering (Online), 2024)
This paper reports the preparation and characterization of (1-x) PbZr0.52Ti0.48O3 -xBiFeO3 (1-x)PZTxBFO) (x= 0.00, 0.15, 0.30, 0.45, 0.60 and 1.00) multiferroic ceramics which were prepared by a sol-gel method for PZT and hydrothermal reaction process for BFO. The perovskite structure of the composite system was confirmed by X-ray diffraction and Raman spectroscopy, while the composite microstructure w:as char:acterized by scanning electron microscopy. XRD results and Rietveld analysis for the (1-x)PZT-xBFO composites confirm the coexistence of these three phases; rhombohedral (R3m) and tetragonal phases (P4mm) for pure PZT and only the rhombohedral phase (R3c) for pure BFO. Raman spectroscopy of the (1-x)PZT-xBFO composites shows two clear bands around 150 and 180 cm-1. When the BFO content increases, the intensities of Raman modes are decreased. The SEM results suggested a formation of agglomerate and form into large complex clusters as BFO increased and a higher grain size was obtained for the BFO sample compared with the other composites. The EDS spectra of our pellets show that all the characteristic lines of the chemical elements Pb, Zr, Ti, and O and Bi, Fe, and O are present for the PZT and BFO materials respectively. The temperature-dependent dielectric constant shows different behavior dependent on BFO content. Indeed, the dielectric properties are found to be improved with an increase in dopant concentration of BFO in PZT, and novel dielectric behavior, resonance, and antiresonance, were obtained.